Autonomous curriculum and EFL motivation and learning : The effects of autonomous curriculum approaches on motivation and learning in EFL : A colombian case study at the Universidad de los Andes (2012)
This is a qualitative case study based in an English as a foreign language (EFL) context within a private research university in Bogotá, Colombia. The objective of this study is to examine the impact of autonomous approaches to language teaching on learner motivation and language development through learner perceptions of these. Specifically, through surveys, learner reflections, and a focus group the study seeks to examine the impact of gradually shifting the locus of control about curricular decisions from teacher to students over the course of three units. Three teaching methodologies, including a teacher-centered approach, Project Based Learning and the Process Syllabus, were used. Results indicated that learners' perceived increased control over classroom decisions as a factor that positively impacted their motivation. Students also noted that when control about curricular decisions was shared between teacher and learner that this balance of power had the most positive effect on learning. These findings raise questions as to how far shifting the locus of control toward students, that is, incorporating student voice into curricular decisions, may positively impact motivation and language development in other language learning contexts. Furthermore, this study offers some curricular approaches and tasks that might help to promote such a shift.